3D multiscale controlled micropatterning of lead-free piezoelectric electroceramics via Epoxy Gel Casting and lift-off. Issue 9 (August 2017) - Kaushal, A.; Olhero, S.M.; Singh, Budhendra; Bhardwaj, Chandan; Sharma, Ishu; Bdikin, Igor; Button, Tim; Ferreira, J.M.F.
Abstract: We report on the fabrication of multiscale three-dimensional (3D) micropatterning of 0.5Ba(Zr0.2 Ti0.8 )O3 − 0.5(Ba0.7 Ca0.3 )TiO3 (BZT − BCT) electroceramic material using soft lithographic PDMS moulds. The ceramic microcomponents were successfully consolidated by Epoxy Gel Casting from stable aqueous suspension of BZT-BCT material. A successful aqueous processing of electroceramic material was employed with surface protection of powder particles against hydrolysis as considerably an important parameter to achieve high solid loading suspension with pseudoplastic behaviour suitable for casting in micro scale moulds. The process to obtain micro sized pattern of material was divided in two steps: (i) production of high quality SU-8 master moulds and the respective negative replicas in PDMS (soft mould) by photolithography and soft mould replication, respectively; (ii) casting the soft moulds by stable high solid loading BZT-BCT suspensions in presence of gelation agents followed by de-moulding, drying and sintering. The resulting green micropattern structures show interesting features, including complex structures with a periodic variations through their length and, multiscale array of hexagonal shaped pillars of different aspect ratios (AR) (max AR ≈ 8 with approx ∼320 μm of height and side length ∼40 μm) with smooth side wall features along height. The green pillar arrays were further sintered to show the suitability of aqueous processing of material and proposed casting method.